(untitled) (Heritage, 2020)
This paper analyzes the life and activities of Janko Janković, head of a card files of the IV Anti-Communist Division, the Special Police Department. Janko Janković was originally a Kragujevac resident, where he received his elementary education, after which he moved to Belgrade and started working in the Belgrade City Administration. He first worked as the chief of the General Police department card file, and from 1941 he was transferred to the same position in the Special Police Department. Almost simultaneously, he connected with the Provincial Committee of the Communist Party of Yugoslavia for Serbia and began to inform them of the activities and plans of the Anti-Communist Division of Belgrade City Administration. He actively cooperated with the Communist movement until early October 1943, when he was discovered and arrested, and then executed by shooting on April 27, 1944, in Marinkova bara. It is believed that he helped about 2000 people with his activity. In the paper we tried to objectively analyze his position and activities from the angle of historical science.